Significant delayed aortic dilatation after tetralogy of Fallot repair: a case report - Yosuke Nishimura (Surgical Case Reports, 2020)
Abstract Background Aortic dilatation may occur in some patients even after complete repair of tetralogy of Fallot (TOF). The progression rate of the aortic diameter is so slow, and the incidence of aortic dissection is so low that it is suspected that frequent imaging of the aorta may not be necessary. Case presentation We describe an asymptomatic 41-year-old man with hypertension in whom aortic dilatation was accidentally discovered 39 years after TOF repair. He underwent ambulatory follow-up without any difficulty for 21 years after the repair. Contrast-enhanced computed tomography revealed significant aortic dilatation (maximum diameter of 88 mm at the sinus of Valsalva), and echocardiography revealed severe aortic regurgitation, which seemed to progress during the last 18 years without any evaluation or follow-up. The Bentall procedure was successfully performed using a valved graft, under deep hypothermic circulatory arrest with antegrade cerebral perfusion, and his postoperative course was uneventful. Histopathological examination of ascending aorta specimens revealed severe cystic medial degeneration. Conclusions Keeping in mind that a patient with rapid progression of the aortic dilatation after TOF repair exist, periodic follow-up for evaluation of the aorta is essential in patients with TOF.